2015
DOI: 10.4081/jlimnol.2015.1078
|View full text |Cite
|
Sign up to set email alerts
|

Local factors affecting the testate amoeba community (Protozoa: Arcellinida; Euglyphida) in a neotropical floodplain

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…Arcellidae is commonly recorded as one of the most representative families of testate amoebae in Neotropical ecosystems in terms of richness and abundance of species (Vucetich, 1973;Panarelli, Casanova, Nogueira, Mitsuka, & Henry, 2003;Fulone, Vieira, Velho, & Lima, 2005; Lansac-Tôha, Robertson, & Joko, 2008;Escobar, Brenner, Whitmore, Kenney, & Curtis, 2008;Oliveira & Hardoim, 2010;Arrieira, Alves, Schwind, & Lansac-Tôha, 2015). This family is characterized by specimens with shells made up of endogenous material, with discoid or hemispherical shape and centered pseudostoma (Souza, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Arcellidae is commonly recorded as one of the most representative families of testate amoebae in Neotropical ecosystems in terms of richness and abundance of species (Vucetich, 1973;Panarelli, Casanova, Nogueira, Mitsuka, & Henry, 2003;Fulone, Vieira, Velho, & Lima, 2005; Lansac-Tôha, Robertson, & Joko, 2008;Escobar, Brenner, Whitmore, Kenney, & Curtis, 2008;Oliveira & Hardoim, 2010;Arrieira, Alves, Schwind, & Lansac-Tôha, 2015). This family is characterized by specimens with shells made up of endogenous material, with discoid or hemispherical shape and centered pseudostoma (Souza, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The most representative exogenous testate amoebae families recorded in these lakes (Difflugiidae and Centropyxidae) also exhibited high species diversity on Neotropical floodplains (Arrieira, Alves, Schwind, & Lansac‐Tôha, ; Lansac‐Tôha et al, ; Schwind, Arrieira, Simões, Bonecker, & Lansac‐Tôha, ). On the other hand, the families Lesquereusidae, Phryganellidae, and Plagiopyxidae showed a smaller number of species as they have a restricted distribution and low presence in the planktonic environment (Velho, Lansac‐Tôha, Bonecker, & Zimmermann‐Callegari, ).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown that the presence of these families is frequently recorded in freshwater environments (Green, 1975;Dabés, 1995;Landa and Mourguês-Schurter, 2000), particularly in the Upper Paraná River basin (Lansac-Tôha et al, 2004Alves et al, 2010Alves et al, , 2012Arrieira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%